2016
DOI: 10.1515/cdbme-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Open air plasma deposited antimicrobial SiOx/TiOx composite films for biomedical applications

Abstract: Open air atmospheric pressure plasma jet (APPJ) enhanced chemical vapour deposition process was used to deposit biocompatible SiO x /TiO x composite coatings. The as deposited films are hydrophilic and show visible light induced photocatalytic effect, which is a consequence of the formation of defects in the TiO x structure due to the plasma process. This photocatalytic effect was verified by the demonstration of an antimicrobial effect under visible light on E. coli as well as by degradation of Rhodamine B. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…In addition, the surface chemistry of biomaterials, such as wettability, is known to influence cell responses. Hydrophilic silicon oxide and titanium oxide are often used as coatings for implanted devices due to their good biocompatibility 20 , 21 . Surface energy of the ECM can control fluid interactions, cell adhesion, and protein adsorption, thus influencing tissue formation 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the surface chemistry of biomaterials, such as wettability, is known to influence cell responses. Hydrophilic silicon oxide and titanium oxide are often used as coatings for implanted devices due to their good biocompatibility 20 , 21 . Surface energy of the ECM can control fluid interactions, cell adhesion, and protein adsorption, thus influencing tissue formation 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Most atmospheric pressure plasma approaches involved an aerosol-assisted strategy in which a liquid suspension of the fillers and the matrix precursors is atomized and injected in the form of an aerosol in the plasma discharge [14,16,[18][19][20][21] or postdischarge. [22,23] The aerosol-assisted plasma deposition enabled to embed a wide range of fillers (e.g., metal nanoparticles, [16,22] oxide nanoparticles, [20,23] or enzymes [19,21] ) in a variety of matrix compositions (e.g., plasma-polymerized hexamethyldisiloxane, [16,20] alkenes, [19,21] or pyrrole [19] ). On the other hand, the plasma curing of liquid layers has also enabled the embedment of various fillers (cyclodextrines, [24] metalloporphyrins, [25,26] coordination polymers nanoparticles, [15] TiO 2 and CeO 2 nanoparticles [27] ) for sensing [24,25] or optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilic silicon oxide and titanium oxide are often used as coatings for implanted devices due to their good biocompatibility. 20,21 Surface energy on ECM can control uid interaction, cell adhesion, and protein adsorption, thus in uences tissue formation. 22 It had been reported that surface with a contact angle of ~ 70° provided the best control of cell behaviors.…”
Section: Introductionmentioning
confidence: 99%